Análise metabólica e metabolômica de atleta olímpico: uma nova proposta para um nexus bioquímico - Resende, Nathália Maria (2010)
The metabolomics is an area of science "omics" that characterizes the phenotypes of the metabolites and the connection of these with their corresponding genotypes, allowing the identification of the metabolome of an individual. This metabolomics research allows to view the rapid responses of the biochemical and biological analysis of metabolism in any situation, whether environmental change, pathological, genetic or in response to exercise stress. This study aims main to present the mass spectrometry together with the clinical laboratory as a research tool for obtaining the metabolome of an athlete's Olympic Windsurfing Class RS:X. During exercise, the energy demand is increased by requiring changes in metabolism, and thus the metabolism provides answers to these various metabolic modifications. Therefore, analytical techniques, such as laboratory tests and mass spectrometry may be used for the metabolic evaluation, allowing to investigate and intervene in a scientific manner, the exercise prescription, control and monitoring of athlete training, helping with interventions to adaptation of physical exercise in improving their athletic performance.